Today's Academic Research: The Role of ChatGPT Writing - Chukwuere, Joshua Ebere (Universitas Bina Darma, 2024)
The purpose of this study is to examine the place of ChatGPT writing in the current academic environment. Significant attention has been drawn to the amazing capacity of ChatGPT, a sophisticated language model created by OpenAI, to produce text answers that nearly mimic human speech. The current study examines ChatGPT's effects on a number of academic areas, including writing support, data analysis, literature reviews, and scientific cooperation. The paper looks at the benefits and drawbacks of using ChatGPT in academic research and offers some insight into prospective uses for this technology in the future. To efficiently respond to the research questions and accomplish the stated goals, the present study used a quick review of the literature technique. The study has discovered several ChatGPT uses in academic writing, including data gathering, teamwork, implications, and restrictions. The study also looked at how to prevent plagiarism in written work produced using ChatGPT. In conclusion, if ChatGPT is used wisely and responsibly, it has the potential to dramatically enhance and revolutionize academic research, enabling multidisciplinary cooperation.